T-pattern analysis of offensive and defensive actions of youth football goalkeepers - Santos, Fernando; Santos, João; Espada, Mário; Ferreira, Cátia; Sousa, Paulo; Pinheiro, Valter (Frontiers in Psychology, 2022)
Nowadays, football goalkeeper´s (GKs) play an important role in the team´s organization, namely considering the offensive and defensive process. The purpose of our investigation focusesed on the notational and T-patterns analysis of the offensive and defensive actions of elite young football GKs. The participating GKs (n=3, Mean years of age16.6) presented 8 years of experience in the specific position, were international selected for the national team of Portugal and compete in the national U-17 championship of Portugal. Thirty games were observed. The observational sample consisted of defensive actions (n=225) and offensive actions (n=296). Two observational instruments were used to codify the actions: Observation system of defensive technical- tactical actions of GKs and Observation system of offensive technical- tactical actions of GKs. Both instruments underwent a validation process, and inter- and intra-observer reliability was tested. The codification of the actions was performed with LINCE program, and later the data were exported to Microsoft Excel and THEME 5.0. The notational data was analyzed in SPSS and T-patterns detection analysis in THEME 5.0. The young observed GKs predominantly actions were fundamentally goal defense and participation in the team’s offensive process construction through actions performed with the foot and hand. The analysis of T-patterns allowed to identify standard actions in the defensive actions of goal defense and exit of the goal, as well as related to the defense of tactical schemes. In the offensive process, through the analysis of T-patterns it was reinforced the participation of the GK in the team first phase of construction, in the execution of goal kicks and actions that start as a result of actions of the opponent. The GKs defensive actions are mostly focused on the objective of goal defense and offensive actions with the hands and feet are important in the participation in positional attack construction. Our study contributes to a better knowledge of the GKs actions in the competition and is relevant to be considered by the specific position coaches in the training process organization.